Evaluation of Nurses' Ethical Attitudes in Care - Yasemin Özyer Güvener; Ebru Özcan (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study was conducted to determine nurses' ethical attitudes in care and factors related to ethical attitudes. Method: This research is a cross-sectional and descriptive type research. The research was conducted with 155 nurses working in a public hospital in the Central Black Sea region. Data were collected face to face using the Ethical Attitudes in Nursing Care Scale and Socio-Demographic Survey Form. Descriptive statistics, Mann-Whitney U, Kruskal Wallis test were used to analyze the data. Results: The average age of the individuals participating in the study was 35.97 (S=8.83). It was determined that 83.2% of the nurses received ethics-related training during their undergraduate education. It was determined that the average HBETÖ score of the nurses participating in the research was 151.79 (SD=19.49). A statistically significant relationship was found between gender and education level and scale scores (p<0.05). No statistically significant relationship was found between age, field of study, duration of employment, and taking ethics courses and scale scores. Conclusion: In this study, it was determined that nurses had positive ethical attitudes in care. It was determined that there was a relationship between education level and gender and ethical attitudes, and that the ethical attitudes of female and postgraduate nurses were more positive.